2018
DOI: 10.1016/j.bpj.2018.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Organization of Apolipoprotein-A-I-Derived Peptides within Disc-like Arrangements

Abstract: Apolipoprotein A-I is the major protein component of high-density lipoproteins and fulfils important functions in lipid metabolism. Its structure consists of a chain of tandem domains of amphipathic helices. Using this protein as a template membrane scaffolding protein, class A amphipathic helical peptides were designed to support the amphipathic helix theory and later as therapeutic tools in biomedicine. Here, we investigated the lipid interactions of two apolipoprotein-A-I-derived class A amphipathic peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 72 publications
(128 reference statements)
1
16
0
1
Order By: Relevance
“…These biophysical studies show that magainin 2 adopts very stable alignments parallel to the membrane surface under all conditions tested so far (Bechinger, 2011;Salnikov and Bechinger, 2011;Strandberg et al, 2013), a feature also observed for many other related peptides (Porcelli et al, 2013;Resende et al, 2014;Perrin et al, 2015;Salnikov et al, 2018). In contrast to magainin 2, the membrane topological alignment of PGLa is modulated by the detailed composition of the phospholipid membrane, its peptide-to-lipid ratio, the hydration level or the presence of magainin 2 (Tremouilhac et al, 2006;Salnikov and Bechinger, 2011;Strandberg et al, 2013).…”
Section: Introductionsupporting
confidence: 67%
“…These biophysical studies show that magainin 2 adopts very stable alignments parallel to the membrane surface under all conditions tested so far (Bechinger, 2011;Salnikov and Bechinger, 2011;Strandberg et al, 2013), a feature also observed for many other related peptides (Porcelli et al, 2013;Resende et al, 2014;Perrin et al, 2015;Salnikov et al, 2018). In contrast to magainin 2, the membrane topological alignment of PGLa is modulated by the detailed composition of the phospholipid membrane, its peptide-to-lipid ratio, the hydration level or the presence of magainin 2 (Tremouilhac et al, 2006;Salnikov and Bechinger, 2011;Strandberg et al, 2013).…”
Section: Introductionsupporting
confidence: 67%
“…When membranes are uniaxially oriented relative to the magnetic field of the NMR spectrometer, a unique molecular alignment is retained, spectral resolution is recovered, and the resulting anisotropic chemical shifts and dipolar and quadrupolar interactions provide valuable information about the orientation of bonds, protein domains, and polypeptides as a whole. Thus, the corresponding spectra can be used to analyze the structure, dynamics, and topology of membrane-associated polypeptides (Das et al 2015;Gopinath et al 2015;Itkin et al 2017;Salnikov et al 2018).…”
Section: Solid-state Nmr Investigations Of Polypeptidesmentioning
confidence: 99%
“…Whereas the 15 N chemical shift alone provides an approximate tilt angle of helical domains (Bechinger and Sizun 2003), the combination with 2 H solid-state NMR spectra from methyldeuterated alanines results in accurate tilt and pitch angle information (Fig. 4.3) Salnikov et al 2018).…”
Section: Solid-state Nmr Investigations Of Polypeptidesmentioning
confidence: 99%
“…Thus, the detailed topology found in this work agrees with the peptides forming the rim of nanodiscs in a double-belt arrangement. 25 An important observation is that the head-to-tail orientation of these peptides around the edge of discoidal structure strongly support the interaction of π-electron containing aromatic rings for the stabilization of discoidal structures.…”
Section: Design Of Shorter Apoa-i Mimetic Peptides and Interaction Wimentioning
confidence: 94%